Technical Issues for the Fabrication of a CN-HCCB-TBM Based on RAFM Steel CLF-1 - 王平怀 谌继明 付海英 刘实 李雄伟 许增裕 (Plasma science & technology, 2013)
Reduced activation ferritic/martensitic steel （RAFM） is recognized as the primary candidate structural material for ITER＇s test blanket module （TBM）. To provide a material and property database for the design and fabrication of the Chinese helium cooled ceramic breeding TBM （CN HCCB TBM）, a type of RAFM steel named CLF-1 was developed and chaxacter~zed at the Southwestern Institute of Physics （SWIP）, China. In this paper, the R＆D status of CLF-1 steel and the technical issues in using CLF-1 steel to manufacture CN HCCB TBM were reviewed, including the steel manufacture and different welding technologies. Several kinds of property data have been obtained for its application to the design of the ITER TBM.